The diagnostics of the energy coupling efficiency in the Fast Ignition integrated experiment. (March 2016) - Arikawa, Y.; Fujioka, S.; Morace, A.; Zhang, Z.; Nagai, T.; Taga, M.; Abe, Y.; Kojima, S.; Sakata, S.; Inoue, H.; Utsugi, M.; Hattori, S.; et al.
Abstract: The energy coupling efficiency (CE) in Fast Ignition (FI) laser fusion was studied at GEKKO XII and LFEx laser facility by using newly developed targets and plasma diagnostic instruments. The gated-liquid scintillator neutron detectors had been upgraded by using neutron collimators for intense background fluxes of γ-rays and neutrons in the FI experiment. Clear fusion neutron signal was successfully recorded in the sub-kJ heating FI experiment. Up to 5 times neutron yield enhancement was observed, and the CE of the heating laser to core plasma was estimated to be 1.6% for cone-in-shell target implosion by 9 beams and core heating by LFEX pulse 115 ps before bang time. The laser-to-electron energy conversion efficiency was separately diagnosed using a newly developed target and resulted to be 45%. The fast electron energy spectrum was estimated to be 2.3 MeV slope temperature by hard x-ray spectroscopy. Monte Carlo simulations demonstrate the consistency of the data set.